190k views
1 vote

(x + 1 )/(2) = (7x - 3)/(2)
Solve it ok please .​

User PoulsQ
by
4.8k points

2 Answers

2 votes

Answer:


\sf x =(2)/(3)

Step-by-step explanation:


\sf \rightarrow (x+1)/(2) = (7x-3)/(2)

cross multiply


\sf \rightarrow 2(x+1) = 2(7x-3)

divide both sides by 2


\sf \rightarrow x + 1 = 7x-3

isolate variables


\sf \rightarrow x -7x = -3-1

simplify


\sf \rightarrow -6x = -4

divide both sides by -6


\sf \rightarrow (-6x)/(-6) = (-4)/(-6)

simplify


\sf \rightarrow x =(2)/(3)

User Kraego
by
5.7k points
1 vote

Answer:


x=(2)/(3)

Step-by-step explanation:

Given equation:


(x+1)/(2)=(7x-3)/(2)

Step 1: Multiply both sides by
2.


\implies 2\left((x+1)/(2)\right)=2\left((7x-3)/(2)\right)


\implies x+1=7x-3

Step 2: Subtract
7x from both sides.


\implies x-7x+1=7x-7x-3


\implies -6x+1=-3

Step 3: Subtract
1 from both sides.


\implies -6x+1-1=-3-1


\implies -6x=-4

Step 4: Divide both sides by
-6 and simplify.


\implies (-6x)/(-6)=(-4)/(-6)


\implies x=(4)/(6)=\boxed{(2)/(3)}

User Avj
by
4.9k points